Child Compared with Parent Perceptions of Child-Level Food Security - Landry, Matthew J (Curr Dev Nutr, 2019)
BACKGROUND: There is a need to directly and accurately conceptualize and measure food insecurity in children as part of surveillance and public health efforts. OBJECTIVE: The aim of this study was to compare parent and child perceptions of child-level food security status via questionnaires within a large, ethnically diverse population. METHODS: Cross-sectional baseline data from a cluster-randomized controlled trial involving primarily low-income, Hispanic third- to fifth-grade students and their parents were used for analysis. The sample consisted of 2408 dyadic (parent and child) pairs. Parents completed the 8-item child-referenced Household Food Security Survey Module and their responses were compared with an adaption of the 5-item Child Food Security Assessment completed by their child. Levels of association between child and parent perceptions within dyads were calculated using Goodman and Kruskal's γ statistic. A mixed-effects binomial logistic regression model was used to model discordance as a function of child, parent, and household sociodemographic characteristics. RESULTS: The child sample was 53% girls, mean age of 9 y, and 63% were Hispanic. The parent sample was 86% women and 65% Hispanic. Child and parent perceptions of child-level food security agreed only 21.7% of the time. There was a weak positive association between child and parent perceptions of child-level food security (γ = 0.162, P < 0.001). Children perceived themselves as less food secure than their parents’ perception 70.1% of the time. Household receipt of Supplemental Nutrition Assistance Program benefits was associated with greater odds of discordant food security perceptions, whereas female children, older children, and parents not working were characteristics associated with lower odds of discordant perceptions. CONCLUSIONS: Results, in combination with the existing literature, suggest that parent perceptions of child-level food insecurity may underestimate child-level food insecurity experiences. Inaccurate estimations or underestimations of the true prevalence of child-level food insecurity could be detrimental to maternal and child health efforts. This trial was registered at clinicaltrials.gov as NCT02668744.